Modification of bismuth phosphate based nanomaterial as sunlight sensitive photocatalysts - Ng, Jit Jang (2021)
This research highlighted Bismuth Phosphate (BiPO4) photocatalysts’ modification to enhanced solar-driven photocatalysis for endocrine-disrupting compounds. Pure BiPO4 was prepared through a simple sol-gel approach. Incorporation of graphitic carbon nitride (g-C3N4) and Silver (Ag) nanoparticles onto BiPO4 via simple thermal deposition and photodeposition, respectively. The BiPO4/g-C3N4 was synthesized with different g-C3N4 loading weight percentages: 0.5wt%, 1.5wt% and 2.5wt% whereas the weight percentages for Ag/BiPO4 were 1.0wt%, 3.0wt% and 5.0wt%. Field Emission Scanning Electron Microscope (FESEM) and High-Resolution Transmission Electron Microscopy (HRTEM) investigated the surface morphology while the XRD investigated the structure and particle size of as-prepared BiPO4/g-C3N4 and Ag/BiPO4. UV-vis Diffuse Reflectance Spectra (UV-DRS) spectrum depicted increment of dopant loading weight percentages leads to increasing light absorption of as-synthesized photocatalysts. Furthermore, Time-Resolved Photoluminescence (TRPL) spectra show the charge carrier lifetime increased with high dopant loading. Photodegradation of 2,4-Dichlorophenols (2,4-DCPs) was conducted to investigate the photodegradation efficacy of BiPO4/g-C3N4 and Ag/BiPO4 in the presence of natural sunlight. With 1.0g of each photocatalyst being added into 50ppm of 2,4-DCPs. The results concluded that both g-C3N4 and Ag nanoparticles present in BiPO4 manage to enhance the photocatalytic activity under sunlight irradiation compared to pure BiPO4. In addition, the results for photodegradation of 2,4-DCPs matched well with the characterization results of UV-DRS and TRPL spectra which agreed that the highest dopant loading weight percentage of g-C3N4 and Ag possesses the highest light absorption and lowest recombination rate of electron-hole pairs. After 90 min of 2,4-DCPs photodegradation, 0.5wt%, 1.5wt% and 2.5wt% of BiPO4/g-C3N4 achieved 55%, 77% and 100% of 2,4-DCP removal, respectively. On the other hand, 69%, 66%, 76% of 2,4-DCPs photodegradation efficiency after 5hr were achieved by 1.0wt% Ag/BiPO4, 3.0wt% Ag/BiPO4, and 5.0wt% Ag/BiPO4, respectively. The enhanced photodegradation of 2,4- DCPs under sunlight irradiation is mainly contributed by prolonged the charge carriers' lifetime by incorporation with g-C3N4. Moreover, the existence of gC3N4 further enhanced the light absorbance to harvest the entire sunlight energy and produce excessive active radicals. Besides that, Ag's incorporation acted as an electron trap to separate the electrons and holes produced in BiPO4 under sunlight excitation. This separation prevented the generated electrons and holes from recombining to form heat. Therefore, Ag nanoparticles’ presence retarted the recombination formation, allowing free electrons to react and form active radicals responsible for the degradation of 2,4-DCPs. A scavenging test was conducted to determine the active radical species. Superoxide anion (O2 -) and holes (h+ ) radical are the main active radicals for BiPO4/g-C3N4. Similarly, O2 - and hydroxyl (•OH) radicals are responsible for the photodegradation for Ag/BiPO4. A recycling test was conducted to investigate the stability and reusability of both as-synthesized photocatalysts. Photodegradation efficiency of 2.5wt% BiPO4/g-C3N4 and Ag/BiPO4 retained above 70% after four cycles of photocatalytic activities.